Skin and self‐injury: a possible link between peripheral innervation and immune function?. (4th September 2014) - Symons, Frank J; Gilles, Elizabeth; Tervo, Raymond; Wendelschafer‐Crabb, Gwen; Panoutsopoulou, Ioanna; Kennedy, William
<x xml:space="preserve">Abstract</x> The aim of this preliminary case study series was to investigate epidermal innervation in pediatric patients with significant neurological impairment and self‐injurious behavior. We enrolled four pediatric patients with self‐injury (two males, two females; mean age 12y, range 9–14y) and used archival specimens from healthy, age‐matched children with typical development for comparison purposes. Epidermal nerve fiber density, peptide content, and mast cell degranulation patterns from non‐damaged skin were tested between the patients and the comparison group. The male patients with self‐injury had significantly increased epidermal nerve fiber densities, increased substance P positive fiber count and extensive mast cell degranulation compared with sex‐ and age‐matched individuals with typical development. Our case series shows for the first time altered peripheral innervation from non‐damaged tissue in children with significant self‐injury and developmental disability compared with a healthy comparison group. Establishing the role of peripheral nociceptive and immune modulatory neural pathways may offer new treatment avenues for this devastating neurobehavioral disorder.